Use of PCR to determine Toxoplasma gondii in milk samples from camels (Camelus dromedarius), cattle (Bos taurus) and buffalos (Bubalus bubalis) in East Azarbaijan province, Iran. Issue 1 (20th December 2022) - Asiyabi Aghdam, Somayyeh; Hajipour, Nasser; Moosavy, Mir‐Hassan
Abstract: Background: Toxoplasmosis as a zoonotic condition is developed by an intracellular protozoan parasite Toxoplasma gondii from the Apicomplexa phylum, which imposes economic losses on herds of animals and severe complications in immunocompromised people and pregnant women. This infectious disease can be transmitted to human beings from the contaminated unpasteurized milk, uncooked meat, water and food contaminated with sporulated oocysts and transplacental transmission. Objectives: This study amid to determine T. gondii DNA in camel, buffalo and cow milks in using the PCR method based on the B1 gene. Methods: A total of 100 milk samples, including 55 cows, 30 buffalos and 15 camels, were collected from different regions of north‐western using direct milking and then transferred to the Food and Aquatic Health Laboratory under refrigerated conditions. Results: The results showed that out of 100 milk samples examined, 5 samples (5%) were contaminated, and T. gondii DNA was detected in the milk samples of 2 (3.63%) cows, 1 (3.33%) buffalos and 2 (13.33%) camels, respectively. Conclusions: Our findings reveal that raw milk contaminated with T. gondii can be an important route of transmission of infection for human beings. Abstract : Toxoplasma gondii is a food‐borne zoonotic parasite that infects humans. The results demonstrate the presence of the DNA of T. gondii in buffalo, cow and camel's milk. Consumption of raw milk of different animals can be a risk factor for human health. To prevent infection with T. gondii, it is recommended to boil milk before consumption.